PENGALAMAN REMAJA PEREMPUAN KORBAN PERUNDUNGAN ONLINE (CYBERBULLYING) DI MEDIA SOSIAL - Asri Bryllianissa, Fadhilla; Hasfi, Nurul; Gono, Joyo (Interaksi Online, 2024)
The background in this research is women who are victims of online bullying or cyberbullying on social media. Understand the informant's experience of cyberbullying incidents through the communication process, then what impacts they receive after experiencing cyberbullying behavior. There are two theories used in this research, New Media Theory and Standpoint Theory. The method used in the research is descriptive qualitative, using a phenomenological approach and interpretive paradigm, where this research is to see how victims of cyberbullying act as research subjects. The research subjects were six informants who experienced cyberbullying on social media. The results of this research found that Instagram was a forum for cyberbullying carried out by the perpetrator, where the perpetrator who carried out the cyberbullying was someone closest to the victim. From here the communication experience that occurred between the subject and the perpetrator had three phases in the communication process. New Media Theory proves that the cyberbullying experiences received by victims are mostly found on social media Instagram. Where in New Media Theory media has the nature of being easily manipulated. Cyberbullying perpetrators do this by spreading information on Instagram that is related to the victim, and it is spread widely and is believed by many people even though the truth has not been proven. Standpoint Theory reveals that women who are victims of cyberbullying do not have space to clarify the cyberbullying incidents they experienced.